Vpeljava prevzete terminologije ter njene etimološke razlage v pouk geografije - Jemec, Sara (Geografija v šoli, 2024)
Terminology (i. e., borrowed technical vocabulary) in classroom can impede the teacher and the learner, as its abstractness and complexity often require in-depth understanding. This fact led us to design a study comparing the origins of borrowed geography terms and analysing the preference for adopting subject-specific vocabulary in geography instruction. The linguistic findings suggest that Latin has contributed more to geography terminology than Greek, both in the case of physical and sociogeographical terminology. Despite some reservations, teachers and students favour introducing and using borrowed terminology.
Keywords: borrowed terminology; Etimologija; Geografija; geografska terminologija; interdisciplinarity; interdisciplinarnost; pouk geografije; school geography